1996
DOI: 10.1016/1357-2725(95)00166-2
|View full text |Cite
|
Sign up to set email alerts
|

Ostrich (Struthio camelus) carboxypeptidase B: Purification, kinetic properties and characterization of the pancreatic enzyme

Abstract: Carboxypeptidase B has been isolated from numerous mammalian and invertebrate species. In contrast, very little is known about carboxypeptidases of avian origin. To provide information for a comparative study, we have undertaken an investigation of the kinetic and physical properties of ostrich carboxypeptidase B. Carboxypeptidase B from the pancreas of the ostrich was purified by water extraction of acetone powder and aminobenzylsuccinic acid affinity and hydroxylapatite chromatography. The effects of pH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…5). These results confirmed that cpbAs1 encodes an active CPB, and they are consistent with other CPB reports (13,(40)(41)(42). The CPBAs1 kinetic parameters were determined by the progress of an enzyme-catalyzed reaction using fixed amounts of CPBAs1 and a series of different concentrations of Hip-Arg as the substrate according to the standard Michaelis-Menten method.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…5). These results confirmed that cpbAs1 encodes an active CPB, and they are consistent with other CPB reports (13,(40)(41)(42). The CPBAs1 kinetic parameters were determined by the progress of an enzyme-catalyzed reaction using fixed amounts of CPBAs1 and a series of different concentrations of Hip-Arg as the substrate according to the standard Michaelis-Menten method.…”
Section: Resultssupporting
confidence: 72%
“…Moreover, its specificity for Arg is higher than that for Lys residues as reported for other CPBs (13,45). The recombinant CPBAs1 K m is about 8.5-fold greater than the amounts which have been reported for the CPB enzyme of vertebrates by using the same substrates (13,(40)(41)(42). Furthermore, the CPBAs1 alignment with CPB enzymes of other organisms (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…This decrease in pHi might be caused by the increased accumulation of acidic metabolite (e.g., lactic acid), which might outweigh the opposite effect caused by the higher levels of Arg and Lys (Jeong et al 2006). Nevertheless, such a difference in pHi was believed not to significantly affect the activity of basic Cps (Bradley et al 1996;Wolff et al 1962). …”
Section: Discussionmentioning
confidence: 93%
“…A lower pHi value was observed throughout the culture process under higher Arg and Lys concentrations (HH) when compared with the other conditions. However, this difference in pHi (no more than 0.05 unit) was believed not to significantly affect the activity of basic Cps (Bradley et al 1996;Wolff et al 1962). Additionally, extracellular pH (pHe) was also measured during the batch cultures, and no significant difference was observed among the four conditions (data not shown), thus indicating that the different lysine variant levels should not be attributed to pH condition.…”
Section: Variations In Intracellular Ph (Phi)mentioning
confidence: 96%
“…However, lower molecular weights of CPB were reported for cod (26,000) (Overnell, 1973). The optimum pH of the A. pectinifera CPB (pH 7.5) was similar to those of other animal species (pH7-8.2) (Marinkovicet al, 1977;Ajlan & Bailey, 1999;Bradley et al, 1996;Hajjou et al, 1995;Yoshinaka et al, 1984b).…”
mentioning
confidence: 99%